Development of e-commerce applications and integration into the marketplace to support MSME product sales - Sinung Suakanto; Rokhman Fauzi; Rachmadita Andreswari; Margareta Hardiyanti; Widyatasya Agustika Nurtrisha (University of Merdeka Malang, 2022)
Small and Medium Enterprise (SMEs) is a business run by a single person, household, or a small business entity. The production volume and market share of SMEs are certainly small. SMEs need to be considered so that they can increase their trading volume. This community service activity is a follow-up activity from the previous implementation of e-commerce named as Gambung Store. One of the obstacles of this e-marketplace is that there were small customers even though the products being sold already exist. This community service activity is carried out to increase market share. One of them is by integrating independent marketplace applications with large marketplaces. The method used is the method of developing information systems and systems integration. By integration, SMEs sellers can more easily make sales to various marketplaces with single window without having to visit one by one to large marketplaces. This activity has resulted in a system capable of integrating as well as digital marketing activities that are expected to help further introduce SMEs products. The results of analytical data from digital marketing activities can also be seen as a form of results from this activity to help introduce SMEs products to the public.